Assessing the Liability Convention and the Indonesian Space Act in Light of Active Debris Removal - Ardes, Runggu Prilia; Nugraha, Ridha Aditya (Hasanuddin Law Review, 2020)
As the orbit in outer spaceÂ becomesÂ denser, the drive to actively preserve the outer space increases. Active debris removal is the answer to this issue. It serves solemn purposes to maintain the space environment and prevent collision between space objects. This action requires high-level technology and techniques whichÂ makeÂ it prone to accidents. This article examines the applicability of Liability Convention of 1972 and Indonesian Space Act of 2013 for active debris removal and whether its provisions are sufficient for any future legal issues on this matter. A normative juridical method is used for the analysis. The Space Act from other States like France and Austria will also be briefly mentioned and compared to. At the end, it is concluded that although both of the legal instruments are suitable and applicable for active debris removal, there are still some essential aspects that need to be defined namely property and proof of fault. The paper suggests that it should be emphasized that onlyÂ cataloguedÂ debris can be regarded as property, and that the term â€œfaultâ€ at the minimum should have a modest definition that captures the â€œdeviation from the normal operationâ€.